Attachment style, COVID-19, and impression formation : how individual differences and external experiences influence the Halo effect - Lim, Yun Yee (Nanyang Technological University, 2021)
The halo effect has been liberally used to understand how people make judgments about others. Despite the body of literature on the topic, little is known about how individual differences and experiences influence someone's tendency to rely on irrelevant information when forming impressions. This is especially more poignant amid the global COVID-19 pandemic, where personal differences may cloud the perception of social distancing or other new pandemic policies. This study predicts that viewer perception (halo effect) is more strongly influenced by stimuli of opposite genders, secure or anxious-preoccupied attachments, and the priming of close social interactions. It investigates the possibility of individual differences modulating the effects of priming on viewer perception. Participants (N = 289, Mean Age = 29.0 ± 12.0) rated the aesthetic appreciation and trustworthiness of a series of ninety-six faces (N = 96) before and after watching a priming video demonstrating social interaction, social distancing, or a neutral condition. It was found that individual attachment styles affect the Halo Effect’s strength. However, gender and age did not significantly influence impression formation. The study was pre-registered on the Open Science Framework and approved by the ethics review board of the Nanyang Technological University. These findings' relevance for user interface and web design is considered, and implications for future cognitive theories are discussed.